IL-27 Driven Upregulation of Surface HLA-E Expression on Monocytes Inhibits IFN-γ Release by Autologous NK Cells. (10th March 2014) - Morandi, Fabio; Airoldi, Irma; Pistoia, Vito
Abstract : HLA-G and HLA-E are HLA-Ib molecules with several immunoregulatory properties. Their cell surface expression can be modulated by different cytokines. Since IL-27 and IL-30 may either stimulate or regulate immune responses, we have here tested whether these cytokines may modulate HLA-G and -E expression and function on human monocytes. Monocytes expressed gp130 and WSX-1, the two chains of IL27 receptor (R), and IL6Rα (that serves as IL-30R, in combination with gp130). However, only IL27R appeared to be functional, as witnessed by IL-27 driven STAT1/ STAT3 phosphorylation. IL-27, but not IL-30, significantly upregulated HLA-E (but not HLA-G) expression on monocytes. IFN-γ ; secretion by activated NK cells was dampened when the latter cells were cocultured with IL-27 pretreated autologous monocytes. Such effect was not achieved using untreated or IL-30 pretreated monocytes, thus indicating that IL-27 driven HLA-E upregulation might be involved, possibly through the interaction of this molecule with CD94/NKG2A inhibitory receptor on NK cells. In contrast, cytotoxic granules release by NK cell in response to K562 cells was unaffected in the presence of IL-27 pretreated monocytes. In conclusion, we delineated a novel immunoregulatory function of IL-27 involving HLA-E upregulation on monocytes that might in turn indirectly impair some NK cell functions.